Jupiter’s atmospheric jet streams extend thousands of kilometres deep - Kaspi, Y.; Galanti, E.; Hubbard, W. B.; Stevenson, D. J.; Bolton, S. J.; Iess, L.; Guillot, T.; Bloxham, J.; Connerney, J. E. P.; Cao, H.; Durante, D.; Folkner, W. M.; et al. (Nature (London), 2018)
The determination of Jupiter’s odd gravitational harmonics by the Juno spacecraft reveals that the observed jet streams extend to about three thousand kilometres below the cloud tops. Probing the depths of Jupiter The Juno mission set out to probe the hidden properties of Jupiter, such as its gravitational field, the depth of its atmospheric jets and its composition beneath the clouds. A collection of papers in this week's issue report some of the mission's key findings. Jupiter's gravitational field varies from pole to pole, but the cause of this asymmetry is unknown. Rotating planets that are squashed at the poles like Jupiter can have a gravity field that is characterized by a solid-body component, plus components that arise from motions in the atmosphere. Luciano Iess and colleagues use Juno's Doppler tracking data to determine Jupiter's gravity harmonics. They find that the north–south asymmetry arises from atmospheric and interior wind flows. To determine the depths of these flows, Yohai Kaspi and colleagues analyse the odd gravitational harmonics and find that the J 3 , J 5 , J 7 and J 9 harmonics are consistent with the jets extending deep into the atmosphere, perhaps as far as 3,000 kilometres. They conclude that the mass of Jupiter's dynamical atmosphere is about one per cent of Jupiter's total mass. The composition of Jupiter beneath its turbulent atmosphere remains a mystery. If different parts of a spinning object rotate at different rates, then the object probably has a fluid composition. Tristan Guillot and colleagues study the even gravitational harmonics and find that, below a depth of about 3,000 kilometres, Jupiter is rotating almost as a solid body. The atmospheric zonal flows extend downwards by more than 2,000 kilometres, but not beyond 3,500 kilometres, as is also the case with the jets. The depth to which Jupiter’s observed east–west jet streams extend has been a long-standing question 1 , 2 . Resolving this puzzle has been a primary goal for the Juno spacecraft 3 , 4 , which has been in orbit around the gas giant since July 2016. Juno’s gravitational measurements have revealed that Jupiter’s gravitational field is north–south asymmetric 5 , which is a signature of the planet’s atmospheric and interior flows 6 . Here we report that the measured odd gravitational harmonics J 3 , J 5 , J 7 and J 9 indicate that the observed jet streams, as they appear at the cloud level, extend down to depths of thousands of kilometres beneath the cloud level, probably to the region of magnetic dissipation at a depth of about 3,000 kilometres 7 , 8 . By inverting the measured gravity values into a wind field 9 , we calculate the most likely vertical profile of the deep atmospheric and interior flow, and the latitudinal dependence of its depth. Furthermore, the even gravity harmonics J 8 and J 10 resulting from this flow profile also match the measurements, when taking into account the contribution of the interior structure 10 . These results indicate that the mass of the dynamical atmosphere is about one per cent of Jupiter’s total mass.